Preparation of sugarcane bagasse nanocellulose hydrogel as a colourimetric freshness indicator for intelligent food packaging. (1st December 2020) - Lu, Peng; Yang, Yang; Liu, Ren; Liu, Xin; Ma, Jinxia; Wu, Min; Wang, Shuangfei
Graphical abstract: Highlights: A freshness indicator in hydrogel state was prepared from bagasse nanocellulose. The indicator displayed a quick color response to the spoilage of chicken. Changes in volatile components during spoilage was detected by electronic nose. Abstract: A sugarcane bagasse nanocellulose-based hydrogel was developed as a colourimetric freshness indicator for monitoring spoilage of chicken breast. Nanocellulose was prepared from sugarcane bagasse cellulose filaments by TEMPO-mediated oxidation, and then used to form a strong self-standing hydrogel matrix through Zn 2+ cross-linking. The hydrogel worked as a carrier for pH-responsive dyes (bromothymol blue/methyl red), which changed colour according to the freshness of the chicken sample. CO2 levels were found to increase with the spoilage of chicken, relative to rising levels of micro-organisms. The indicator hydrogel optical colour changed from green to red on the third day, as the log CFU/g passed the limit of acceptability for human consumption and emission of complicated volatiles. This new design of colourimetric freshness indicator made with a nanocellulose hydrogel has a quick response to chicken spoilage and is expected to facilitate the utilisation of bagasse nanocellulose as a value-added material in intelligent packaging.